Antibacterial nano-composite film capable of promoting wound healing and preparation method and application of antibacterial nano-composite film

By introducing MXene and lignin into PVA hydrogel and forming a crosslinking network through repeated freeze-thawing, a nanocomposite membrane that promotes wound healing was prepared, which solved the problems of low mechanical strength and poor antibacteriality of PVA wound dressings, and achieved good wound healing effect and biocompatibility.

CN119679994AActive Publication Date: 2025-03-25LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411860447.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing PVA wound dressings have low mechanical strength and poor antibacterial properties, making it difficult to effectively promote wound healing.

Method used

By introducing MXene and lignin into the PVA hydrogel system, a cross-linking network is formed by repeatedly freezing and thawing, a nanocomposite membrane that is antibacterial and promotes wound healing is prepared.

Benefits of technology

This nanocomposite membrane has good mechanical properties, biocompatibility, electrical conductivity and antibacterial activity, which can significantly promote wound healing and has no obvious biotoxicity in the body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119679994A_ABST
    Figure CN119679994A_ABST
Patent Text Reader

Abstract

The invention discloses a nano-composite membrane capable of resisting bacteria and promoting wound healing as well as a preparation method and application of the nano-composite membrane. The nano-composite membrane is obtained by repeatedly freezing and thawing a mixed solution of polyvinyl alcohol, lignin and MXene to form a cross-linked network, wherein the mass ratio of the polyvinyl alcohol to the lignin to the MXene is 1: 4: (0.0025-0.04). According to the invention, MXene and LS are introduced into a PVA hydrogel system, so that the composite membrane is endowed with good mechanical properties, biocompatibility and antibacterial activity, the composite membrane has moderate swelling property and conductivity, and the nano composite membrane provided by the invention is non-toxic and has good chemical stability. The nano-composite membrane can promote wound healing, remarkably reduce inflammatory response, promote formation of new vessels and enhance nutrient substance delivery, can further promote wound healing in combination with electrical stimulation, and shows a wide application prospect in the field of wound dressings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nano composite film, in particular to an antibacterial and wound healing promoting nano composite film and a preparation method and application thereof. Background Art

[0002] The treatment of skin wounds is crucial to human health, so the development of new wound dressings with excellent performance has been a hot topic in the medical field in recent years. Traditional wound dressings such as bandages, gauze and other natural fibers are passive dressings. Their fiber structure can absorb exudate to keep the wound dry, but they are prone to adhesion and have no antibacterial function. They cannot provide sufficient drainage for the wound and have no obvious effect on promoting wound healing. An ideal wound dressing should have the characteristics of removing excess exudate from the wound, protecting the wound from microbial infection, good mechanical properties, biocompatibility and low price. Since polyvinyl alcohol (PVA) meets most of the characteristics of an ideal wound dressing, it has been used in the development of new wound dressings. However, the low mechanical strength and poor antibacterial properties of PVA limit the widespread use of single PVA in wound dressings.

[0003] Recently, researchers have tried to improve the mechanical properties of PVA hydrogel systems by adding different nanofillers. MXene, as a new type of two-dimensional nanomaterial, has many excellent properties, such as high hydrophilicity, high specific surface area and excellent mechanical properties; at the same time, MXene also has certain antibacterial properties, and its sharp edges can destroy bacterial cell membranes to achieve antibacterial effects. In addition, MXene can promote cell adhesion and proliferation. Therefore, MXene shows broad application potential in the biomedical field. In addition, in order to improve the antibacterial properties of wound dressings, antibiotics are usually added to them, but the problem of antibiotic resistance is becoming increasingly serious.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] The purpose of the present invention is to provide an antibacterial and wound healing promoting nanocomposite film and its preparation method and application, which solves the problems of low mechanical strength and poor antibacterial property of existing PVA. The nanocomposite film of the present invention has good mechanical properties, biocompatibility, conductivity and antibacterial activity.

[0006] In order to achieve the above-mentioned purpose, the present invention provides an antibacterial and wound healing promoting nanocomposite film, wherein the nanocomposite film is obtained by repeatedly freezing and thawing a mixed solution of polyvinyl alcohol, lignin and MXene to form a cross-linked network; wherein the mass ratio of the polyvinyl alcohol, lignin and MXene is 1:4:(0.0025-0.04).

[0007] Preferably, the repeated freezing and thawing conditions are freezing at -20°C for 22 hours and then thawing at room temperature for 2 hours.

[0008] The second object of the present invention is to provide a method for preparing the antibacterial and wound healing promoting nanocomposite film, which comprises: adding polyvinyl alcohol to water, heating and stirring until PVA is completely dissolved to obtain a PVA aqueous solution; then, adding lignin to the PVA solution and stirring to ensure that the lignin is evenly dissolved in the PVA aqueous solution to obtain a PVA / LS mixed solution; adding a MXene dispersed aqueous solution to the PVA / LS mixed solution, stirring, and standing to obtain a PVA / LS / MXene mixed solution; and repeatedly freezing and thawing the PVA / LS / MXene mixed solution to form a cross-linked network.

[0009] Preferably, the concentration of the PVA aqueous solution is 10 wt %.

[0010] Preferably, the concentration of the MXene dispersed aqueous solution is 1 to 16 mg / mL.

[0011] Preferably, polyvinyl alcohol is added to water, heated to 95° C. and stirred until PVA is completely dissolved to prepare a PVA aqueous solution.

[0012] Preferably, the MXene dispersed aqueous solution is added to the PVA / LS mixed solution, stirred for 2 hours, and allowed to stand for 6 hours to obtain a PVA / LS / MXene mixed solution.

[0013] Preferably, the PVA / LS / MXene mixed solution is poured into a mold and frozen at -20°C for 22 hours, then thawed at room temperature for 2 hours, and frozen and thawed repeatedly 2 to 6 times to form a stable cross-linked network.

[0014] The third object of the present invention is to provide the application of the antibacterial and wound healing promoting nanocomposite film in antibacterial and wound healing promoting aspects.

[0015] The antibacterial and wound healing promoting nanocomposite film of the present invention and its preparation method and application solve the problems of low mechanical strength and poor antibacterial property of the existing PVA and have the following advantages:

[0016] (1) The nanocomposite membrane of the present invention introduces MXene and LS into the PVA hydrogel system, which gives the composite membrane good mechanical properties, biocompatibility and antibacterial activity, and it also has moderate swelling properties and conductivity. In addition, the nanocomposite membrane of the present invention is non-toxic and has good chemical stability. It will not be oxidized when placed at room temperature for 28 days.

[0017] (2) The nanocomposite membrane of the present invention has a loose porous structure on the surface and cross-section of the PLM composite membrane, which can provide abundant cell adhesion sites and nutrient delivery channels, thereby achieving the effect of promoting wound healing. In addition, the PLM composite membrane has excellent mechanical properties and good flexibility and stretchability.

[0018] (3) The nanocomposite membrane of the present invention, the PLM composite membrane, can promote wound healing. Animal experiments show that the PLM composite membrane can heal wounds in a shorter period of time; the PLM composite membrane can downregulate the expression of pro-inflammatory factors IL-6 and TNF-α genes, significantly reduce inflammatory reactions, reduce the distribution of inflammatory cells and promote epithelial tissue formation; the PLM composite membrane can also promote the formation of new blood vessels and enhance the transport of nutrients; moreover, the PLM composite membrane has no obvious biological toxicity in vivo and has no obvious effect on the important organs of mice;

[0019] (4) The nanocomposite film of the present invention can be combined with electrical stimulation to further promote wound healing, showing broad application prospects in the field of wound dressings;

[0020] (5) The preparation method of the present invention is a strategy for green synthetic hydrogel wound dressings, that is, a composite film (PLM) of PVA, LS and MXene with excellent antibacterial activity and mechanical properties is prepared by a sol-gel method. Through repeated freezing and thawing, the mixed solution forms a stable and uniform cross-linked network. At the same time, the -OH on the PVA chain and LS forms hydrogen bonds with functional groups on the surface of MXene, such as -OH, -F, and =O. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The figure is a flow chart of the preparation of the PLM composite membrane of the present invention.

[0022] Figure 2 Characterization results of MXene nanosheets prepared in Example 1 of the present invention; (a) transmission electron microscopy; (b) Tyndall effect.

[0023] Figure 3 Characterization results of the PLM composite film prepared in Example 1 of the present invention; (a) XRD spectrum; (b) FTIR spectrum.

[0024] Figure 4SEM morphology photos of the PLM composite film of the present invention with PVA and PL; (a) surface; (b) cross section.

[0025] Figure 5 The flexibility (a) and stretchability (b-d) of the PLM8 composite film of the present invention in a wet state.

[0026] Figure 6 The figures are the plate coating of Staphylococcus aureus and Escherichia coli in the bacterial experiment of the PLM composite film of the present invention with PVA and PL (a); the colony count of Staphylococcus aureus (b); the colony count of Escherichia coli (c); and the inhibition rings of Staphylococcus aureus and Escherichia coli (d).

[0027] Figure 7 It is the conductivity of the PLM composite film of the present invention.

[0028] Figure 8 The swelling curves of the PLM composite film of the present invention with PVA and PL (a); the swelling ratio of the composite film after immersion for 24 hours (b); and the optical photographs of the four mixed solutions before and after standing at room temperature for 28 days (c).

[0029] Fig. 9 These are the CCK-8 test results of the PLM composite film of the present invention, PVA and PL on the 1st, 3rd and 5th days.

[0030] Fig.10 Live cell / dead cell double staining images of L929 cells cultured on the PLM composite membrane of the present invention, PVA and PL for 1, 3 and 5 days (scale bar: 300 μm).

[0031] Fig.11 Optical images of wounds treated with the PLM composite membrane of the present invention combined with electrical stimulation (a) and H&E staining images collected on the 3rd, 9th and 15th days after surgery (b).

[0032] Fig.12 The figures are analysis of TNF-α (a) and IL-6 (b) expressed in the wound tissue of mice when the PLM composite membrane of the present invention acts on the wound tissue, as well as representative images of TNF-α immunofluorescence staining of the tissue on the 3rd and 9th days (c) and representative images of CD31 immunofluorescence staining of the tissue on the 9th and 15th days (d).

[0033] Fig.13 This is an H&E staining image of important organs (heart, liver, spleen, lung, and kidney) of mice on the 15th day after the PLM composite film of the present invention acted on the wound tissue. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0036] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as values, quantities, contents and concentrations, are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0037] The features mentioned in the present invention can be combined arbitrarily, as long as there is no contradiction in the combination of these features, all possible combinations should be considered as the scope of this specification. Each feature disclosed in the specification can be replaced by any alternative feature that can provide the same, equal or similar purpose. Therefore, unless otherwise specified, the disclosed features are only general examples of equal or similar features.

[0038] The present invention provides an antibacterial and wound healing-promoting nanocomposite film, a preparation method and application thereof. The preparation method of the antibacterial and wound healing-promoting nanocomposite film comprises:

[0039] (1) PVA was added to deionized water and magnetically stirred at 95°C until PVA was completely dissolved to prepare a 10 wt% PVA aqueous solution; then, an appropriate amount of LS (lignin) powder was added to the PVA solution and magnetically stirred for 0.5 h to ensure that the LS powder was evenly dissolved in the PVA solution;

[0040] (2) Prepare MXene dispersed aqueous solutions with different concentrations (1 mg / mL, 2 mg / mL, 4 mg / mL, 8 mg / mL, 12 mg / mL and 16 mg / mL), then add them into the PVA / LS mixed solution, stir magnetically for 2 h and let stand for 6 h;

[0041] (3) The mixed solution was poured into a mold and placed in a -20°C refrigerator for 22 h, then thawed at room temperature for 2 h, and the mixture was frozen and thawed repeatedly 2 to 6 times to form a stable cross-linked network (non-covalent cross-linking) to obtain a PLM composite film.

[0042] Because the final product is used as a wound dressing to promote wound healing, it must be made into a film. The mass ratio of PVA, LS, and MXene in the final composite film is 1:4:0.005-0.04.

[0043] The following is a detailed description of an antibacterial and wound healing promoting nanocomposite film provided by the present invention and its preparation method and application through examples and comparative examples.

[0044] The raw materials and reagents used in the following examples and comparative examples are as follows:

[0045] 1) MXene solution: 400-mesh MAX phase was used as raw material and prepared by the affiliated laboratory according to the fluorine-containing etching method (HCl+LiF). Commercially available MXene solution can also be directly used.

[0046] 2) PVA: PVA powder from Thermo Scientific.

[0047] 3) LS: LS powder from BOSF is used.

[0048] Example 1

[0049] A nanocomposite film for antibacterial and wound healing promotion, the preparation method thereof is as follows:

[0050] 2.0 g of PVA was added to 20 mL of deionized water and stirred at 95° C. until the PVA was completely dissolved to prepare a 10 wt % PVA aqueous solution. Then, 8.0 g of LS powder was added to the prepared PVA solution and magnetically stirred for 0.5 h.

[0051] Prepare 5 mL of 1 mg / mL MXene dispersed aqueous solution, add it to the above mixed solution and stir it magnetically for 2 h. After stirring, let it stand for 6 h. Pour the mixed solution into a mold and put it into a -20°C refrigerator to freeze for 22 h, thaw for 2 h, and repeat freezing and thawing 4 times to form a cross-linked network to obtain a PLM-1 composite film.

[0052] Example 2

[0053] A nanocomposite film for antibacterial and wound healing promotion, the preparation method of which is substantially the same as that of Example 1, except that:

[0054] The concentration of the prepared MXene dispersed aqueous solution is 2 mg / mL.

[0055] The prepared composite membrane is recorded as PLM-2 composite membrane.

[0056] Example 3

[0057] A nanocomposite film for antibacterial and wound healing promotion, the preparation method of which is substantially the same as that of Example 1, except that:

[0058] The concentration of the prepared MXene aqueous solution was 4 mg / mL.

[0059] The prepared composite membrane is recorded as PLM-4 composite membrane.

[0060] Example 4

[0061] A nanocomposite film for antibacterial and wound healing promotion, the preparation method of which is substantially the same as that of Example 1, except that:

[0062] The concentration of the prepared MXene dispersed aqueous solution was 8 mg / mL.

[0063] The prepared composite membrane is recorded as PLM-8 composite membrane.

[0064] Example 5

[0065] A nanocomposite film for antibacterial and wound healing promotion, the preparation method of which is substantially the same as that of Example 1, except that:

[0066] The concentration of the prepared MXene dispersed aqueous solution was 12 mg / mL.

[0067] The prepared composite membrane is recorded as PLM-12 composite membrane.

[0068] Example 6

[0069] A nanocomposite film for antibacterial and wound healing promotion, the preparation method of which is substantially the same as that of Example 1, except that:

[0070] The concentration of the prepared MXene dispersed aqueous solution was 16 mg / mL.

[0071] The prepared composite membrane is recorded as PLM-16 composite membrane.

[0072] Comparative Example 1

[0073] A PVA composite film, the preparation method thereof is as follows:

[0074] 1.0 g of PVA was added to 10 mL of deionized water and stirred at 90° C. until the PVA was completely dissolved to prepare a 10 wt % PVA aqueous solution.

[0075] Subsequently, 2.5 mL of deionized water was added to the mixed solution and magnetically stirred for 6 h. After stirring, the mixed solution was poured into a mold and placed in a -20°C refrigerator for 22 h, thawed for 2 h, and frozen and thawed four times to form a cross-linked network; then the PVA composite film was obtained by freeze drying.

[0076] Comparative Example 2

[0077] A PL composite film, the preparation method thereof is as follows:

[0078] 1.0 g of PVA was added to 10 mL of deionized water and stirred at 90° C. until the PVA was completely dissolved to prepare a 10 wt % PVA aqueous solution. Then 4.0 g of LS powder was added to the PVA solution and ultrasonically stirred for 0.5 h.

[0079] Subsequently, 2.5 mL of deionized water was added to the mixed solution and magnetically stirred for 6 h. After stirring, the mixed solution was poured into a mold and placed in a -20°C refrigerator for 22 h, thawed for 2 h, and frozen and thawed four times to form a cross-linked network; then the PL composite film was obtained by freeze drying.

[0080] Experimental Example 1 Material Structure Characterization

[0081] 1. Characterization of prepared MXene nanosheets

[0082] like Figure 2 As shown in (a), MXene exhibits a two-dimensional layered structure with clean and smooth edges under a transmission electron microscope. Figure 1 (b) shows the Tyndall effect of MXene solution, which indicates that MXene flakes have good dispersibility, uniformity and stability in water.

[0083] 2. Characterization of PLM composite films

[0084] like Figure 3 As shown in the figure, (a) XRD spectra and (b) FTIR spectra of the raw materials and composite films are shown, where MAX represents the precursor material of MXene. Figure 3 It can be shown that hydrogen bonds are formed among PVA, LS and MXene.

[0085] 3. Morphology and structure of PLM composite film

[0086] like Figure 4 As shown, SEM morphology photographs of the composite membrane (a) surface and (b) cross-section are shown, indicating that the surface of the composite membrane becomes rough with the addition of LS and MXene, and the cross-section presents a loose and porous morphology.

[0087] Experimental Example 2 Performance Test

[0088] 1. Mechanical properties test

[0089] (1) Qualitative test of tensile properties of PLM composite films

[0090] like Figure 5As shown, the PLM8 composite film has good (a) flexibility and (b-d) stretchability in the wet state (hydrogel produced by freeze-thaw technology without freeze-drying treatment), where (b) and (d) are pictures before and after stretching, and (c) is the picture during stretching.

[0091] (2) Quantitative testing of mechanical properties of PLM composite films

[0092] All mechanical properties of PLM composite hydrogels were tested at room temperature using an electronic universal testing machine (AGS-X, Shimadzu, Japan). Each test was repeated 3 times for each sample, and the average value was calculated.

[0093] Evaluation of tensile properties: The PLM composite film samples prepared in each example were cut into a standard rectangular shape (size: 30 mm × 20 mm × 2 mm). The tensile test was carried out at a constant rate of 5 mm / min, and the tensile strength was calculated based on the maximum load applied / cross-sectional area of ​​the sample, and the elongation at break was calculated according to the following formula: (stretching stroke length at break / initial gauge length) × 100%. The elastic modulus (i.e., Young's modulus) was calculated based on the slope of the initial linear portion of the stress-strain curve.

[0094] Compression strength test: The PLM composite film samples prepared in each example were prepared into a cylinder with a diameter of 15.5 mm and a height of 5 mm. The mixed solution was poured into the cylinder mold during freeze-thaw, and the cylinder sample was obtained after freeze-thaw gelation. Under room temperature, each sample was subjected to 3 repeated compression tests, and the compression strength was calculated based on load / cross-sectional area.

[0095] The results are shown in Table 1. From the experimental results, it can be seen that the MXene concentration has an effect on the tensile strength and elongation at break of the composite film. With the increase of MXene concentration, the elongation at break and tensile strength first increase and then decrease, and the elastic modulus shows an increasing trend.

[0096] Table 1 is a comparison of the properties of the composite membranes prepared in various embodiments of the present invention and comparative examples.

[0097]

[0098]

[0099] 2. Antimicrobial activity test

[0100] The antibacterial properties of the composite membrane were systematically evaluated using the inhibition ring test and colony counting method. The specific experimental process is as follows:

[0101] The sterilized composite membrane (PLM-4, PLM-8, PL or PVA) was cut into a circle (1 cm in diameter). Subsequently, Staphylococcus aureus and Escherichia coli were diluted to appropriate concentrations in the sterilized Luria-Bertani (LB) medium, and the diluted bacterial solution was evenly spread on the agar medium using a sterile applicator. Next, different composite membrane samples after sterilization were placed on the culture medium (a Control group was set up in the experiment, in which no material was added), and incubated at 37°C for 18 to 22 hours, and the formation and size of the antibacterial ring were observed.

[0102] In the colony counting experiment, the diluted bacterial solution and different composite membranes after disinfection and sterilization (a Control group was set up in the experiment, in which no material was added) were placed on a constant temperature shaker at 37°C and cultured together for 18 to 22 hours. Finally, the obtained bacterial solution was further diluted to an appropriate concentration and evenly spread on the agar medium, and then incubated at 37°C for 18 to 22 hours. The bacterial colonies were then counted to evaluate the degree of inhibition of bacterial growth by the composite membrane.

[0103] Results Figure 6 , which are the plate coating of Staphylococcus aureus and Escherichia coli in the bacterial experiment of the PLM composite film of the present invention (a); Staphylococcus aureus colony count (b); Escherichia coli colony count (c); Staphylococcus aureus and Escherichia coli inhibition ring (d). It can be seen that the PLM composite film of the present invention has good antibacterial properties. The results of the colony counting method and the inhibition ring experiment both show that the composite film has good antibacterial ability and has antibacterial activity against both G+ and G- bacteria.

[0104] The colony counts of Staphylococcus aureus and Escherichia coli plate coatings are shown in Table 1. It can be seen that the MXene concentration also has an effect on the antibacterial activity. With the increase of MXene concentration, the antibacterial performance of the PLM composite film against Staphylococcus aureus and Escherichia coli is enhanced.

[0105] 3. Conductivity test

[0106] One side of the PLM composite film prepared in Example 1 was connected to the positive electrode of the battery, and the other side was connected to one end of the light strip, and the other end of the light strip was connected to the negative electrode of the battery, and the luminescence of the light strip was observed.

[0107] Results Figure 7 The PLM composite film of the present invention has good electrical conductivity.

[0108] 4. Chemical stability test

[0109] 1) Swelling test

[0110] Accurately weigh and record the weight (W0) of freeze-dried PVA, PL, PLM-4, and PLM-8 composite membranes, and then soak each group of samples in a predetermined volume of PBS solution at room temperature. Take out the composite membrane at a preset time point (including 0.5h, 1h, 3h, 6h, 12h, and 24h), gently wipe the residual water on the surface of the composite membrane with filter paper, and immediately weigh the weight (Ws) of the composite membrane. Each group of experiments was repeated three times. The swelling rate was calculated based on the following formula:

[0111] Swelling rate (%) = (Ws - W0) / W0 × 100

[0112] 2) Oxidation stability test

[0113] In order to evaluate the effects of PVA and LS on the oxidative stability of freshly prepared MXene solutions, oxidation inhibition experiments were performed as follows:

[0114] First, solutions containing different raw materials were prepared: (a) MXene dispersion; (b) MXene-PVA mixed solution; (c) MXene-LS mixed solution; (d) MXene-PVA-LS mixed solution. After each group of solutions was left at room temperature for 28 days, the solutions were observed to see if they were oxidized.

[0115] Results Figure 8 , (a) is the swelling curve of the PLM composite film of the present invention, (b) is the swelling rate of the PLM composite film of the present invention after immersion for 24 hours, and (c) is a photo of the four mixed solutions before and after standing at room temperature for 28 days. It can be seen that the PLM composite film of the present invention has a lower swelling rate and has good stability when used in an atmospheric environment. Moreover, the MXene-PVA-LS mixed solution has good chemical stability at room temperature and will not be oxidized when left at room temperature for 28 days.

[0116] Experimental Example 3 Biocompatibility Experiment

[0117] The biocompatibility of the composite membrane was evaluated using the CCK-8 test, as follows:

[0118] Mouse fibroblasts (L-929) were selected as model cells. L929 cells were cultured in MEM medium (modified Eagle medium) containing 10% horse serum at 37°C, 95% humidity and 5% CO2. 1.2×10 4L929 cells were cultured for 1, 3, and 5 days, respectively, to detect cell proliferation. At each time point, all the original culture medium in the well plate was gently aspirated, and PBS solution was added. The cells were washed 3 times and the PBS solution was aspirated. Subsequently, CCK-8 reagent was added to the well plate under light-proof conditions and incubated in a cell culture incubator at 37°C for 4 hours under light-proof conditions. After the incubation, the liquid in the well plate was transferred to a 96-cell culture plate, and the absorbance value was measured at 450nm using a multifunctional microplate reader to evaluate the cell number and proliferation status.

[0119] Results Fig. 9 , are the CCK-8 test results of the PLM composite membrane of the present invention on the 1st, 3rd and 5th days. The CCK-8 results show that the amount of cells on the composite membrane is higher, indicating that the PLM composite membrane of the present invention can promote cell proliferation compared with the control group (PVA, PL), and the PLM composite membrane of the present invention has good biocompatibility. Moreover, with the increase of MXene concentration, cell proliferation shows a trend of first increasing and then decreasing.

[0120] Experimental Example 4 Cytotoxicity Test

[0121] By analyzing the above mechanical properties and CCK-8 test results, PLM-4 and PLM-8 composite membranes with excellent mechanical properties and biocompatibility were selected as the experimental group objects for Calcein-AM / PI double staining experiments to evaluate their cytotoxicity, as follows:

[0122] 1.5×10 4 The density of L929 cells was inoculated on different sterilized composite membranes (the NC group was a group with only cells but no composite membrane). At the same time, a group in which L929 cells were directly inoculated in the well plate was set as a blank control group, and the cell survival was observed for 1, 3, and 5 days. At each fixed day, all the original culture medium in the well plate was removed, and PBS solution was added. The cells were washed 3 times and then the PBS solution was removed. Next, the prepared Calcein-AM and PI dyes were added to each well plate to stain the cells, and then the cells were placed in a cell culture incubator at 37°C and incubated for 30 minutes in the dark. The number of living cells was observed under a fluorescence microscope and photographed and recorded.

[0123] Results Fig.10 , are live cell / dead cell double staining images of L929 cells cultured on the PLM composite membrane of the present invention for 1, 3, and 5 days. The calcein-AM / PI live cell / dead cell double staining results show that most of the cells on the composite membrane appear green, that is, these cells are alive, indicating that the PLM composite membrane of the present invention is non-toxic to cells.

[0124] Experimental Example 5 Animal Experiment

[0125] In order to verify the promoting effect of PLM composite membrane on wound healing, the following animal experiments were conducted:

[0126] Thirty-six female Kunming mice weighing between 27 and 30 g were selected as subjects. After two weeks of adaptive feeding in the laboratory environment, the mice were anesthetized by intraperitoneal injection of sodium pentobarbital (dose of 40 mg / kg). Subsequently, the hair on the back of the mice was shaved, the exposed skin was cleaned, and a full-thickness skin wound with a diameter of 7 mm was made on their backs.

[0127] The wound models were randomly divided into 4 groups: control group (only wound model treatment, no composite membrane as wound dressing and electrical stimulation), ES (electrical stimulation) group, PLM group (PLM-8) and PLM+ES group (PLM-8+ES). The ES group and PLM+ES group received 3.6V DC stimulation for 1 hour every day, with the negative electrode placed at the wound site and the positive electrode attached to the normal skin area. During the experiment, the wound size was observed and recorded regularly on days 0, 3, 6, 9, 12 and 15 to compare the healing of wounds under different conditions. In addition, the wound tissues of mice were collected on days 3, 9 and 15, and H&E staining was performed to observe the histological changes of the skin, and the expression of common inflammatory factors TNF-α and vascular endothelial cell marker CD31 was detected by immunofluorescence staining. At the same time, the mRNA levels of inflammatory factors IL-6 and TNF-α were determined by RT-PCR to deeply analyze the cytokine changes in the wound tissues of mice. Finally, on the 15th day of the experiment, the important organs of the mice (including heart, liver, spleen, lung, and kidney) were collected and H&E staining was performed to evaluate the biocompatibility of the PLM composite membrane in vivo.

[0128] Results Figures 11 to 13 , Fig.11 The optical image of the wound of the PLM composite membrane combined with the electrical stimulation ES of the present invention (a) and the H&E staining images collected on the 3rd, 9th and 15th days after surgery (b), Fig.12 The TNF-α analysis (a) and IL-6 analysis (b) expressed in the wound tissue of mice when the PLM composite membrane of the present invention acts on the wound tissue, as well as representative images of TNF-α immunofluorescence staining of the tissue on the 3rd day and the 9th day (c) and representative images of CD31 immunofluorescence staining of the tissue on the 9th day and the 15th day (d), Fig.13 This is an H&E staining image of important organs (heart, liver, spleen, lung, and kidney) of mice on the 15th day after the PLM composite film of the present invention acted on the wound tissue.

[0129] from Fig.11 It can be seen that the PLM composite film of the present invention can promote wound healing. Animal experiments show that the PLM composite film can heal wounds in a shorter period of time.

[0130] from Fig.12 It can be seen that the PLM composite membrane can downregulate the expression of proinflammatory factors IL-6 and TNF-α genes. The RT-PCR experiment showed that the PLM composite membrane can reduce the expression of proinflammatory factors and significantly reduce the inflammatory response. The immunofluorescence results of the endothelial cell marker CD31 showed that the PLM composite membrane can promote angiogenesis in wound tissue, indicating that the PLM composite membrane of the present invention can promote the formation of new blood vessels and enhance the delivery of nutrients. The PLM composite membrane can reduce the distribution of inflammatory cells. The HE staining experiment showed that the PLM composite membrane can reduce inflammatory cells in connective tissue and promote epithelial tissue formation.

[0131] from Fig.13 It can be seen that the PLM composite membrane has no obvious biological toxicity in vivo, and the PLM composite membrane has no obvious effect on the important organs (heart, liver, spleen, lung, and kidney) of mice.

[0132] In summary, the PLM composite film of the present invention not only has good mechanical properties, chemical stability and conductivity, but also has antibacterial effect, good biocompatibility, is non-toxic, can promote wound healing and angiogenesis, has no effect on important organs, and can be combined with electrical stimulation to further promote wound healing, showing broad application prospects in the field of wound dressings.

[0133] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A nanocomposite film for antibacterial and wound healing promotion, characterized in that: The nanocomposite film is obtained by repeatedly freezing and thawing a mixed solution of polyvinyl alcohol, lignin and MXene to form a cross-linked network; Wherein, the mass ratio of polyvinyl alcohol, lignin and MXene is 1:4:(0.0025-0.04).

2. The antibacterial and wound healing promoting nanocomposite film according to claim 1, characterized in that: The repeated freezing and thawing conditions were freezing at -20°C for 22 h and then thawing at room temperature for 2 h.

3. The method for preparing the antibacterial and wound healing promoting nanocomposite film according to claim 1 or 2, characterized in that: The method includes: Add polyvinyl alcohol to water, heat and stir until PVA is completely dissolved, to obtain a PVA aqueous solution; then, add lignin to the PVA solution and stir to ensure that the lignin is uniformly dissolved in the PVA aqueous solution, to obtain a PVA / LS mixed solution; Adding the MXene dispersed aqueous solution to the PVA / LS mixed solution, stirring, and standing to obtain a PVA / LS / MXene mixed solution; The PVA / LS / MXene mixed solution is subjected to repeated freezing and thawing to form a cross-linked network.

4. The preparation method according to claim 3, characterized in that: The concentration of the PVA aqueous solution is 10 wt %.

5. The preparation method according to claim 3, characterized in that: The concentration of the MXene dispersed aqueous solution is 1 to 16 mg / mL.

6. The preparation method according to claim 3, characterized in that: Polyvinyl alcohol was added into water, heated to 95° C. and stirred until PVA was completely dissolved, thereby preparing a PVA aqueous solution.

7. The preparation method according to claim 3, characterized in that: The MXene dispersed aqueous solution was added to the PVA / LS mixed solution, stirred for 2 hours, and allowed to stand for 6 hours to obtain a PVA / LS / MXene mixed solution.

8. The preparation method according to claim 3, characterized in that: The PVA / LS / MXene mixed solution was poured into a mold and frozen at -20°C for 22 hours, then thawed at room temperature for 2 hours, and frozen and thawed repeatedly 2 to 6 times to form a stable cross-linked network.

9. Use of the antibacterial and wound healing promoting nanocomposite film as claimed in claim 1 or 2 in antibacterial and wound healing promoting aspects.

Citation Information

Patent Citations

  • High-strength lignin / polyvinyl alcohol composite antibacterial aquagel and preparation method

    CN110240774A

  • Nano lignin / polyvinyl alcohol composite medical hydrogel and preparation method thereof

    CN113004543A

  • Muscle-fiber-imitating high-toughness antibacterial healing-promoting hydrogel as well as preparation method and application thereof

    CN114539695A

  • Preparation method of high-strength self-healing hydrogel

    CN118221962A

  • Lignin-containing coating composition and ultrafine fibers including the same

    US20170121559A1